Mengkaji Krisis Ekonomi Global Menurut Perspektif Islam - Wening Purbatin Palupi Soenjoto (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2017)
The global economic crisis is an event in which all economic sectors world market collapse or degresi and affect other sectors around the world. The global economic crisis originated from the United States (US), and then spread to almost all countries of the world. In the view of Islam, in fact the economic crisis that the world can not be separated from economic practice at practices or economic activities done contrary to Islamic law. In Islam there are three ways to minimize the economic crisis, namely: Equal distribution of wealth to charity, developing banking with Sharîa’ah system, and a system using the currency dinâr and dirhâm. If three ways really implemented in one country, will likely impact the country can improve the global economic crisis in the country.